School, A Place to Learn Social and Antisocial Behavior - Armin Alimardany; Avishan Alimardany (International Journal of School Health, 2014)
Background: The main goal of sending children to school is to educate and teach them ethical conducts. But do they learn social behaviors out in these schools? Most of students after Entring School and facing new environment and not being monitored by their observant parents become exposed to antisocial behaviors and learn them from their peers. This trend is intensified and hard to control by forming peer groups. Evidence Acquisition: The information and data gathered from library and internet searches. Most articles were searched via sciencedirect.com search engine. Keywords used to access hundreds of papers included antisocial behavior, school and crime, peer groups, age and crime, crime prevention, aggression and violence. The most related articles were selected after consulting and thoroughly reading the downloaded articles. Many articles were excluded owing to their simplistic content and repetitive information. Results: Mounting evidence indicates that schooling can have large amount of unexpected negative effect on pupils. Students learn antisocial behavior from other students and sometimes from their own teachers. Perhaps remarkably, children’s biological changes could manifestly affect their behaviors and turn them into aggressive characters. Conclusions: To date, hundreds of researches have been carried out in order to identify antisocial behavior in schools. It is time to take one step further to minimize these adverse behavioral conducts and shape a moral personality. Therefore, the first step to create a social character during school years is to caution against factors leading to antisocial behaviors including peers. In the next step, implementing appropriate curricula can considerably affect children’s behaviors.